Ultra‐Low Velocity Zone Beneath the Atlantic Near St. Helena - Sefira Davison; Carl Martin; Rita Parai; Sanne Cottaar (Geochemistry, Geophysics, Geosystems)
Abstract There are various hotspots in the Atlantic Ocean, which are underlain by mantle plumes that likely cross the mantle and originate at the core‐mantle boundary. We use teleseismic core‐diffracted shear waves to look for an Ultra‐Low Velocity Zone (ULVZ) at the potential base of central Atlantic mantle plumes. Our data set shows delayed postcursory phases after the core‐diffracted shear waves. The observed patterns are consistent in frequency dependence, delay time, and scatter pattern with those caused by mega‐ULVZs previously modeled elsewhere. Synthetic modeling of a cylindrical structure on the core‐mantle boundary below St. Helena provides a good fit to the data. The preferred model is 600 km across and 20 km high, centered at approximately 15° South, 15° West, and with a 30% S‐wave velocity reduction. Significant uncertainties and trade‐offs do remain to these parameters, but a large ULVZ is needed to explain the data. The location is west of St. Helena and south of Ascension. Helium and neon isotopic systematics observed in samples from this region could point to a less‐outgassed mantle component mixed in with the dominant signature of recycled material. These observations could be explained by a contribution from the Large Low Shear Velocity Province (LLSVP). Tungsten isotopic measurements would be needed to understand whether a contribution from the mega‐ULVZ is also required at St. Helena or Ascension.